Delayed Replantation of Avulsed Tooth - Masoumeh Aminizadeh; Raziyeh Shojaiepoor; Reza Aminizadeh (Negah Institute for Scientific Communication, 2016)
This is a case of delayed replantation of avulsed maxillary central incisor after an extended dry extra-alveolar period. A 10-year-old boy presented with avulsed maxillary central incisor after a fall that resulted in dental trauma, occurring 18 hours earlier. Treatment guidelines for avulsed mature permanent teeth with prolonged extraoral time were carried out for the teeth and the extraoral endodontic treatment was completed. After having been repositioned, the tooth was stabilized for 6 weeks and prophylactic antibiotic was prescribed. Clinical and radiographic controls were done during the next 12 months. During the follow-up period, the tooth remained in a stable, functional position but revealed clinical initial replacement resorption and ankylosis.